LEGAL RISKS AND MITIGATION IN ESTABLISHING A LIMITED LIABILITY COMPANY THROUGH FOREIGN DOMESTIC JOINT VENTURE AGREEMENT - Adinda Marianti; Elisatris Gultom (RADJA PUBLIKA, 2025)
This study analyzes the legal risks and benefits in establishing a limited liability company (PT) through a joint venture scheme between Foreign Direct Investment (PMA) and Domestic Investment (PMDN) in Indonesia. The research uses qualitative methods by reviewing legal documents such as Joint Venture Agreements (JVA) and Articles of Association (AoA), as well as Indonesian investment regulations. The study identifies key risks including inconsistencies between JVA and AoA, disproportionate governance structures, conflicting objectives between PMA and PMDN, and violations of foreign ownership limits under the Positive Investment List. These risks potentially cause operational conflicts and legal sanctions. Additionally, differences in legal backgrounds increase the chance of misinterpretation of ambiguous contract clauses. To mitigate these risks, the research suggests harmonizing the JVA and AoA, involving legal advisors familiar with Indonesian law and international business practices, and implementing clear governance and dispute resolution mechanisms such as arbitration. The findings aim to guide stakeholders in managing joint ventures effectively and legally compliant in Indonesia. Penelitian ini menganalisis risiko hukum dan manfaat pembentukan Perseroan Terbatas (PT) melalui skema joint venture antara Penanaman Modal Asing (PMA) dan Penanaman Modal Dalam Negeri (PMDN) di Indonesia. Metode yang digunakan adalah kajian kualitatif terhadap dokumen hukum seperti Perjanjian Joint Venture (JVA), Anggaran Dasar (AD), serta regulasi investasi di Indonesia. Hasil penelitian mengidentifikasi risiko utama berupa ketidaksesuaian JVA dan AD, struktur tata kelola yang tidak proporsional, perbedaan tujuan antara PMA dan PMDN, serta pelanggaran batas kepemilikan asing sesuai Daftar Positif Investasi. Risiko ini berpotensi menimbulkan konflik operasional dan sanksi hukum. Selain itu, perbedaan latar belakang hukum memperbesar kemungkinan salah tafsir klausul kontrak. Untuk mitigasi, disarankan penyusunan JVA dan AD secara harmonis dengan pendampingan penasihat hukum yang memahami hukum Indonesia dan praktik bisnis internasional, serta mekanisme penyelesaian sengketa yang jelas seperti arbitrase. Temuan ini bertujuan membantu pihak terkait dalam mengelola joint venture secara efektif dan sesuai hukum di Indonesia.